Hepatic iron load differs strikingly between peritoneal dialysis and hemodialysis patients - Guy Rostoker; Mireille Griuncelli; Nasredine Ghali; Séverine Beaudreuil; Yves Cohen; Belkacem Issad (RDPLF, 2019)
Introduction Iron overload is one of the most controversial topics in the management of anemic dialysis patients. Parenteral iron supplementation is commonly prescribed to hemodialysis (HD) patients but less frequently to peritoneal dialysis (PD) patients. Moreover, ferritin targets are far lower and more physiological in PD than in HD.  Methods We compared the liver iron concentration (LIC) measured by means of Signal-Intensity ratio (SIR) magnetic resonance imaging (MRI) according to Rennes University method in a cohort of 32 PD patients living in the Paris region published in 2017, with two cohorts of French HD patients studied in the same way (119 patients reported in 2012 and 80 further patients reported in 2014). Results Normal hepatic iron load (LIC ≤ 50 µmol/g of dry weight) was observed in 81.3% of the 32 PD patients (CI: 64.3-91.5%), as compared to only 16% (CI: 10.4-23.7%) in the first HD cohort and 35% (CI: 25.4-45.9%) in the second HD cohort (p<0.0001 for both comparisons; X2 test). Mild iron overload (50 < LIC ≤ 100 µmol/g) was found in 5 PD patients and severe overload (LIC > 200 µmol/g) in only one PD patient (who had received IV iron) (3.1%; CI: 0-17.1%). Conversely, severe iron overload was found in 30.3% of patients in the first HD cohort (CI: 22.7-39%) and 11.3% of those in the second HD cohort (CI: 5.8-20.2%) (p= 0.0033 versus the first HD cohort, X2 test). Conclusion Contrary to hemodialysis patients, iron overload is rare and mostly mild in peritoneal dialysis patients.